2007
DOI: 10.1109/tcomm.2007.898848
|View full text |Cite
|
Sign up to set email alerts
|

Nonpreemptive Scheduling of Optical Switches

Abstract: Abstract-Many high-speed routers today use Input-Queued (IQ) architectures with a crossbar switching fabric based on optical technology. Packets in the input queues are divided into cells of unit length and the goal is to find a schedule of minimum makespan that forwards all packets to the output ports. The problem is complicated since in optical switches so called configuration delay, that is the time required to reconfigure the switching fabric, is non-negligible with respect to the cell transmission time. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
43
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 27 publications
1
43
0
1
Order By: Relevance
“…The most interesting and general result for the MEC problem is due to Kesselman and Kogan [18] who proposed the following greedy algorithm: Algorithm KK 1. Let E = e 1 , e 2 , .…”
Section: We Call a Solutionmentioning
confidence: 99%
See 4 more Smart Citations
“…The most interesting and general result for the MEC problem is due to Kesselman and Kogan [18] who proposed the following greedy algorithm: Algorithm KK 1. Let E = e 1 , e 2 , .…”
Section: We Call a Solutionmentioning
confidence: 99%
“…In [18], it has been shown that Algorithm KK is a 2-approximation one and an example has been presented yielding an approximation ratio of 2 − 1 ∆ . By a slightly tighter analysis we prove here the next lemma.…”
Section: We Call a Solutionmentioning
confidence: 99%
See 3 more Smart Citations